The Labor Market Impact of Undocumented Immigrants: Job Creation vs. Job Competition - Christoph Albert (Center for Economic Studies and ifo Institute (CESifo), 2017)
This paper explores the impact of undocumented as opposed to documented immigration in a model featuring search frictions and non-random hiring that is consistent with novel empirical evidence presented. In this framework, undocumented immigrants' wages are the lowest of all workers due to their ineligibility for unemployment benefits and lower wage bargaining power. A rise in the share of immigrant workers leads to the creation of additional jobs, but also more job competition. The job creation effect is large for undocumented, while small and potentially negative for documented immigration. Model simulations show that the job creation effect of undocumented immigration is large enough to dominate the competition effect, resulting in gains in terms of both employment and wages for natives, which does not hold for documented immigration. Stricter immigration enforcement mutes job creation and raises the unemployment rate of all workers, having an even larger detrimental effect if it targets employed workers because this leads to a risk premium in their wages. Finally, I present empirical evidence that supports the qualitative predictions of the model.
Keywords: J31; J61; J63; J64; 330; wage gap; migrant workers; hiring; employment